The relationship between Non-Governmental Organizations (NGOs) and Community-Based Organizations (CBOs), in implementing development projects in Mozambique. - Chilengue, Nárcya Da Piedade A. M. (My University, 2014)
This study describes and reflects on the partnership between Non-Governmental Organisations (NGOs) and Community-Based Organisations (CBOs) in implementing development projects in Mozambique. This is a qualitative case study, whose methods of data collection were in-depth semi-structured interviews and document analysis. The study was conducted with two NGOs (one international and one national) and with four CBOs and it took place in Nampula and Gaza provinces and the capital Maputo. The data were analyzed using quantitative method. NGOs and CBOs are different entities in terms of their levels of actuation, responsibilities, nature, and also differ in terms of resources, such as access to information, funding sources and human resources. These differences have raised questions around the possibility of the establishment of an equitable and properly functioning partnership between entities that differ so much in na}ure. The NGOs depend majorly on external funds to support the CBOs; however they also rely on their own funds or funds made available by local funders' institutions. Equally, the CBOs also undertake, some income activity generation, whose income is used for their own institutional expenses and also to support some community needs, though they rely mostly on funds provided by the NGOs. The central idea of this study is that despite the differences between NGOs and CBOs they can establish a balanced partnership based on the recognition of the contribution of each partner and on the significance both attribute to the partnership. The differences constitute the basis of the partnership which in turn allows the acquisition of mutual benefits, recognition and sharing of power. In terms of theoretical framework, I have used Agency theory wherein the NGO is the "Principal" which in a relationship governed by a contract delegates the CBOs as the "Agent" of the implementation of projects in the communities. vii The results showed that the partnership between NGOs and CBOs is characterised by complementarities, mutual benefits, exchange, contribution, and sharing of power by both. The partnership is also based on recognition of the weaknesses, strengths and value of each pa1iner which give place to a balanced partnership. However being a balanced partnership it is also characterised by conflicts that result from the difference of interest between NGOs and CBOs. Risk constitutes another element that characterizes this partnership since the NGOs delegate the CBOs the implementation of the project and not always the CBOs will perform as it is advocated in the contract. Though, as the partnership is valuable for both, NGOs and CBOs will engage in developing strategies for minimising the potential risk in order to maintain and maximise the partnership. The data also showed that the locus of conflict and risk are essentially linked to misusage of money. Since the CBOs implement the project and are institutionally independent from the NGOs, the NGOs develop some strategies of control to ensure that the CBOs will act in accordance of what the contract advocates. It is within these strategies wherein the conflict arises, especidlly because the CBOs do not always understand some of the strategies adopted by NGOs to ensure the accomplishment of the contract what led the CBOs also to adopt some strategies of resistance. In terms of power and decision-making the data showed that both exercise different kind of power and the CBOs influence the decision-making process, though the NGOs showed to have greater control over the process. The contribution of this study to the existing literature lies in the fact that it brings a different approach to the power relations between NGOs and CBOs, which is usually seen as a relationship of the exercise of power by the NGOs over the CBOs. The study seeks to show that the strategies of resistance, counter power and negotiation developed by the CBOs constitute a different form of exercise of power and influence. It also shows that the CBOs are not passive actors in the partnership because they develop strategies to influence and attract the NGOs in the establishment of partnership and decision-making throughout the project cycle.
Keywords: Community development--Mozambique.; Non-governmental organizations--Mozambique.; Mozambique--Social conditions.